Instagram Brand Activation for Fashion Start Ups with Experiential Marketing - Prianka, Dian (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
A lot of startup brands utilized Instagram to build their brand online and to raise awareness toward their brand. Fashion industry is one of the many industries that rely on Instagram heavily. Three Levels of Experiential Marketing was a new strategy that was built from 5 Strategic Experiential Modules (SEMs) from Schmitt such as Sense, Feel, Think, Act and Relate to make the 5 SEMs easily applicable to businesses in Instagram. To validate the application of those Three Levels of Experiential Marketing strategy, startup brands from Faculty of Creative Industry, in Fashion and Product Lifestyle Design program utilized the modules to help build their fashion brand from scratch. There are 20 subjects of students in Fashion and Lifestyle Product Design program in University of Surabaya. These subjects start their own fashion branding on Instagram and utilized the Three Levels of Experiential Marketing Strategy for 1 month. In conclusion, not every factor can be fully embedded, and factors under Sense, Feel and Relate SEMs are the most effective ones.